2022
DOI: 10.3390/en15197096
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flow and Heat Transfer of a Discontinuous Single Started Helically Ribbed Pipe

Abstract: In the present study, the turbulent flow field and the heat transfer in a single started helically ribbed pipe with a discontinuous rib are investigated. A large-eddy simulation (LES) technique is applied in a pipe section with cyclic boundary conditions. The aim of this study is to explain and further analyze the findings from the heat transfer measurements at such complex structures with the help of detailed flow simulations. The simulation results are validated with measurements at a Reynolds number of Re =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, Mousavi et al [25] described a variety of passive methods used to intensify the heat transfer process. Kugele et al [26] used the LES approach for a single-started helically ribbed pipe and validated the velocity and heat transfer between the ribs using experimental data obtained by Virgilio et al [27,28]. The authors considered an acrylic glass with two different helical turbulators inserted into the pipe.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Mousavi et al [25] described a variety of passive methods used to intensify the heat transfer process. Kugele et al [26] used the LES approach for a single-started helically ribbed pipe and validated the velocity and heat transfer between the ribs using experimental data obtained by Virgilio et al [27,28]. The authors considered an acrylic glass with two different helical turbulators inserted into the pipe.…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…They simulated 3D water flow in a pipe at a constant Re = 21,000 and Pr = 7.0, assuming constant thermophysical properties. Kugele et al [26] demonstrated that the LES simulations gave fairly accurate results for the flow field, the level of turbulence, and the local heat transfer coefficient. Measurements and simulations of the Nusselt number in the pipe with and without helical turbulators confirmed a significant increase in the Nusselt number.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 1 more Smart Citation